A STUDY ON MEASURING SOCIAL PERSPECTIVE TAKING OF INDONESIAN NAVY OFFICER - wiwin dwi handayani; Mareyke M.W. Tairas; Nur Ainy Fardana Nawangsari (Universitas Ahmad Dahlan, 2019)
This research was about the Social Perspective Taking instrument which was adapted from a instrument developed by Diazgranados and friends in 2016, by adjusting the setting of the Indonesian Navy. Procedures used with the cross-cultural adaptation stage started from the process of translating to field testing (Beaton, Bombardier, Guillemin, & Ferraz, 2000). Subject involved 120 Navy officers with the rank of major. Sampling using simple random sampling techniques and statistical tests were SEM analysis. The results of the study were all valid items (loading factor> 0.5) and reliable indicators. Goodness of fit model was quite good. This instrument is expected to detect the right candidate for officers and assist the process of preparing officers to become leaders whose decisions are not solely based on knowledge from military education, but also consider perspectives on the thoughts, feelings and behavior of others. The weakness of this instrument is the item in the form of open questions, so it requires more time and effort compared to similar tests with answer choices.Â Keywords: social perspective taking, instrument, officer